Ras-ERK-ETS inhibition alleviates neuronal mitochondrial dysfunction by reprogramming mitochondrial retrograde signaling. - Duncan, O.F.; Granat, L.; Ranganathan, R.; Singh, V.K.; Mazaud, D.; Fanto, M.; Chambers, D.; Ballard, C.G.; Bateman, J.M. (PLoS Genetics, 2018)
Mitochondrial dysfunction activates the mitochondrial retrograde signaling pathway, resulting in large scale changes in gene expression. Mitochondrial retrograde signaling in neurons is poorly understood and whether retrograde signaling contributes to cellular dysfunction or is protective is unknown. We show that inhibition of Ras-ERK-ETS signaling partially reverses the retrograde transcriptional response to alleviate neuronal mitochondrial dysfunction. We have developed a novel genetic screen to identify genes that modify mitochondrial dysfunction in Drosophila. Knock-down of one of the genes identified in this screen, the Ras-ERK-ETS pathway transcription factor Aop, alleviates the damaging effects of mitochondrial dysfunction in the nervous system. Inhibition of Ras-ERK-ETS signaling also restores function in Drosophila models of human diseases associated with mitochondrial dysfunction. Importantly, Ras-ERK-ETS pathway inhibition partially reverses the mitochondrial retrograde transcriptional response. Therefore, mitochondrial retrograde signaling likely contributes to neuronal dysfunction through mis-regulation of gene expression.